Repeated double-poling sprint training in hypoxia by competitive cross-country skiers - Faiss, R.; Willis, S.; Born, D.-P.; Sperlich, B.; Vesin, J.-M.; Holmberg, H. C.; Millet, G. P. (Medicine & Science in Sports & Exercise, 2015)
Purpose: Repeated-sprint training in hypoxia (RSH) was recently shown to improve repeated-sprint ability (RSA) in cycling. This phenomenon is likely to reflect fiber type-dependent, compensatory vasodilation, and therefore, our hypothesis was that RSH is even more beneficial for activities involving upper body muscles, such as double poling during cross-country skiing.